Pemikiran Filsafat Tasawuf Mulla Sadra - Rodiallah, Alkaf; Khudori Soleh, Achmad (Institut Agama Islam Al-Hikmah Tuban, 2023)
Abstract, Mulla Sadra is one of the Islamic figures recognized by the world regarding his philosophical thoughts, Mulla Sadra calls Islamic philosophy Al-Hikmah al-muta'aliah. Mulla Sadra's philosophical thoughts originate from the Koran and Hadith and he changes the way of thinking of someone who so far has thought that philosophy only provides absurd doctrines. This study aims to find out Mulla Sadra's way of thinking through philosophy based on the Al-Quran and Hadith and also knowing the nature of God and humans. This writing uses literature review, namely the appearance of scientific reasoning arguments. The library sources used are books, articles and previous research journals that are relevant to the theme of this subject. As well as using descriptive analysis based on Mulla Sadra's thoughts. The results of the study show that 1) Al-hikmah Al-muta'aliyah is a philosophical teaching that examines a study through rational thinking, a study that can be proven rationally and by analogy but the study still does not depart from Islamic law. 2) Having four spiritual journeys in Mulla Sadra's concept and a person is able to do it if he has cleansed his heart from all contents of the world 3) Knowledge can be obtained by humans according to Mulla Sadra in two ways: first is hard work, second is getting inspiration from the creator while Surahwardi knowledge is intrinsically holy, so humans need to purify themselves first, and also God who has no limits and does not depend on anything. Keywords: Spiritual Journey; Philosophy of Islamic Education; God and Human Knowledge